Definitive chemoradiotherapy for advanced cervical cancer: should it be different in the elderly?. (September 2015) - Caires, Inacelli Queiroz de Souza; Souza, Karla Teixeira; Negrão, Marcelo Vailati; de Oliveira, Julia Andrade; Barroso-Sousa, Romualdo; de Lima, Rafael Caires Alvino; Hoff, Paulo Marcelo Gehm; Diz, Maria del Pilar Estevez
Abstract: Background: Cervical cancer (CC) is the second most common cancer in Brazilian women, and approximately 10% of cases occur in elderly patients (pts). In this age group, disease is usually diagnosed in more advanced stages and oncological therapies are usually less intensive, due to comorbidities and impaired performance status. Methods: Retrospective analysis of pts ≥65 years old with CC admitted at a Brazilian University Cancer Center from August 2008 to February 2012. We performed a descriptive analysis of baseline performance status (PS), disease stage (FIGO), histology, body mass index (BMI), treatment received and overall survival, using the Kaplan–Meier method. Results: 900 medical records were analyzed and 75 pts (8%) fulfilled the inclusion criteria. Median age was 73.4 years old (±5.5 years). Squamous cell carcinoma (SCC) was the most common histology (71 pts, 94.7%). 67 (89.3%) had PS 0 or 1 and 52 pts (69.3%) were eutrophic (BMI 18.5–25 kg/m 2 ). At presentation, disease staging consisted of 18 pts (24%) stage I, 35 pts (46.7%) stage II, 8 pts (10.7%) stage III, 12 pts (16%) stage IVa and 2 pts (2.7%) stage IVb. 24 pts (32%) underwent surgery (hysterectomy, adnexectomy, pelvic and paraaortic lymphadenectomy). Adjuvant treatment with radiotherapy (RT) was performed in 13 pts (total dose of external RT in pelvis ranged from 39.6 to 45 Gy, parametrial boost ranged from 14 to 20 Gy and 4 inserts from 7 to 7.5 Gy of brachytherapy); 8 of them received concomitant platinum-based chemotherapy (CT). 30 pts underwent definitive CRT, 17 definitive RT, 1 palliative CT and 3 best supportive care. In the CRT group, 18 pts received cisplatin (CDDP 40 mg/m 2 /w/6w) and 12 carboplatin (AUC 2/w/6w). During definitive CRT, treatment was discontinued in 39% of pts who received CDDP and 25% of pts who received carboplatin, all due to treatment toxicities. CDDP was associated with more nefrotoxicity (5 pts, 28%) than carboplatin (1 pt, 8.3%). The CDDP group also presented more radiodermatitis and stroke. However, myelosuppression and diarrhea were similar in both groups. After a 26.1-month follow-up, median OS was not reached. Conclusions: Despite advanced age, more than 60% of pts underwent complete CRT treatment. Thus, age should not be the only factor to guide therapeutic decisions in CC. Carboplatin was better tolerated than CDDP in CRT group, but prospective trials are necessary to evaluate the best treatment option in this population.